Synergy of ruthenium metallo-intercalator, [Ru(dppz)2(PIP)]2+, with PARP inhibitor Olaparib in non-small cell lung cancer cells - Yusoh, Nur Aininie; Chia, Suet Lin; Saad, Norazalina; Ahmad, Haslina; Gill, Martin R. (Nature Publishing, 2023)
Poly(ADP-ribose) polymerase (PARP) are critical DNA repair enzymes that are activated as part of the DNA damage response (DDR). Although inhibitors of PARP (PARPi) have emerged as small molecule drugs and have shown promising therapeutic effects, PARPi used as single agents are clinically limited to patients with mutations in germline breast cancer susceptibility gene (BRCA). Thus, novel PARPi combination strategies may expand their usage and combat drug resistance. In recent years, ruthenium polypyridyl complexes (RPCs) have emerged as promising anti-cancer candidates due to their attractive DNA binding properties and distinct mechanisms of action. Previously, we reported the rational combination of the RPC DNA replication inhibitor [Ru(dppz) 2 (PIP)]2+ (dppz = dipyrido[3,2- a :2′,3′- c ]phenazine, PIP = 2-(phenyl)-imidazo[4,5- f ][1,10]phenanthroline), “Ru-PIP”, with the PARPi Olaparib in breast cancer cells. Here, we expand upon this work and examine the combination of Ru-PIP with Olaparib for synergy in lung cancer cells, including in 3D lung cancer spheroids, to further elucidate mechanisms of synergy and additionally assess toxicity in a zebrafish embryo model. Compared to single agents alone, Ru-PIP and Olaparib synergy was observed in both A549 and H1975 lung cancer cell lines with mild impact on normal lung fibroblast MRC5 cells. Employing the A549 cell line, synergy was confirmed by loss in clonogenic potential and reduced migration properties. Mechanistic studies indicated that synergy is accompanied by increased double-strand break (DSB) DNA damage and reactive oxygen species (ROS) levels which subsequently lead to cell death via apoptosis. Moreover, the identified combination was successfully able to inhibit the growth of A549 lung cancer spheroids and acute zebrafish embryos toxicity studies revealed that this combination showed reduced toxicity compared to single-agent Ru-PIP.